Obstacles and Challenges in Implementing Hospital Management Information System (A Study of Public and Private Hospitals in Padang City) - Sari ZA, Ayulia Fardila; Putri, Saliya Oryza; Alifa, Juliza Nurul; Siswati, Sri (Journal of Public Health for Tropical and Coastal Region, 2025)
.Introduction: Digital transformation in the health sector requires hospitals to implement the Hospital Management Information System (HMIS); however, problems remain in its implementation. This study aimed to analyze the obstacles and challenges in implementing an HMIS in Padang City. Methods: This descriptive qualitative study was conducted between March and July, 2024. The study was conducted in two hospitals in Padang City: one public hospital and one private hospital. The research participants were 16 people who were identified through purposive sampling. Data were collected through in-depth interviews, observations, and review of documents. Data processing consisted of data collection, reduction, and presentation, with content analysis. Source and method triangulation were used to ensure data validity.Results: Public hospitals have conducted internal training and have an adequate IT team, while private hospitals do not have formal training and lack IT personnel. From an organizational perspective, public hospitals show strong managerial support in the form of budget allocation and cross-unit coordination, whereas private hospitals face limitations in the integration of Electronic Medical Records (EMR) and SATUSEHAT. In terms of technology, both hospitals face obstacles due to slow Internet networks, but public hospitals are better prepared in terms of hardware infrastructure.Conclusion: The success of an HMIS implementation depends heavily on the alignment of human, organizational, and technological aspects. Private hospitals require stronger support in terms of training, infrastructure, and policies to compete with public hospitals in the digital transformation of health care services.